Influence of interface condition on spin-Seebeck effects. (8th April 2015) - Qiu, Z; Hou, D; Uchida, K; Saitoh, E
Abstract: The longitudinal spin-Seebeck effect (LSSE) has been investigated for Pt/yttrium iron garnet (YIG) bilayer systems. The magnitude of the voltage induced by the LSSE is found to be sensitive to the Pt/YIG interface condition. We observed a large LSSE voltage in a Pt/YIG system with a better crystalline interface, while the voltage decays steeply when an amorphous layer is introduced at the interface artificially.